Transcriptome analysis of luminal breast cancer reveals a role for LOL in tumor progression and tamoxifen resistance. Issue 3 (19th February 2019) - Sun, Wei; Xu, Xiaoen; Jiang, Yizhou; Jin, Xi; Zhou, Ping; Liu, Yirong; Guo, Yajie; Ma, Ding; Zuo, Wenjia; Huang, Shenglin; He, Xianghuo; Shao, Zhiming
Abstract : Luminal breast cancer (BC) has a sustained risk of late disease recurrence and death. Considerable numbers of patients suffer from antiendocrine therapy resistance. Here, we identified a novel lncRNA whose expression is high in breast cancer and especially higher in luminal breast cancer, dubbed LOL (lncRNA of luminal), that acts as a natural sponge for let‐7 microRNAs to regulate tumor growth and tamoxifen resistance. LOL overexpression in parental MCF‐7 cells exhibited a proliferative advantage in the addition of tamoxifen than negative control. Knocking down LOL in TamR MCF‐7 cells, recovered the sensitivity of cells to tamoxifen. Strikingly, we demonstrated that LOL is transcribed from a genomic locus of an enhancer to maintain its high expression in luminal BC and that it is extremely sensitive to enhancer‐regulating factors, such as ZMYND8 and BRD4. Estrogen deprivation or ERα signaling pathway blockage can further stimulate LOL expression, which can promote tumor progression. Clinical analysis of 374 luminal breast cancer samples indicated that LOL is an independent prognostic factor for poor survival in luminal BC. In conclusion, targeting LOL using preclinical/clinical drugs, such as BRD4 inhibitors, may represent a promising approach to inhibit luminal breast cancer progression and tamoxifen resistance. Abstract : What's new? Luminal breast cancer makes up two‐thirds of all breast cancers, and carries an increased risk of relapse after 5 years. These authors identified a novel lncRNA associated with luminal breast cancer, which they dubbed LOL (lncRNA of luminal). Overexpression of LOL, they found, allows cells to resist tamoxifen; knocking down LOL restores tamoxifen sensitivity. They also showed that reducing estrogen receptor alpha (ERα) expression upregulated LOL, and ERα overexpression caused no change in LOL. Inhibiting LOL, they suggest, could help stop tamoxifen resistance and cancer recurrence.